Prognostic value of pretreatment (18)F-FDG PET-CT in radiotherapy for patients with hepatocellular carcinoma - Jo, In Young (Radiat Oncol J, 2015)
PURPOSE: The purpose of this study was to investigate the predictable value of pretreatment (18)F-fluorodeoxyglucose positron emission tomography-computed tomography ((18)F-FDG PET-CT) in radiotherapy (RT) for patients with hepatocellular carcinoma (HCC) or portal vein tumor thrombosis (PVTT). MATERIALS AND METHODS: We conducted a retrospective analysis of 36 stage I-IV HCC patients treated with RT. (18)F-FDG PET-CT was performed before RT. Treatment target was determined HCC or PVTT lesions by treatment aim. They were irradiated at a median prescription dose of 50 Gy. The response was evaluated within 3 months after completion of RT using the Response Evaluation Criteria in Solid Tumors (RECIST). Response rate, overall survival (OS), and the pattern of failure (POF) were analyzed. RESULTS: The response rate was 61.1%. The statistically significant prognostic factor affecting response in RT field was maximal standardized uptake value (maxSUV) only. The high SUV group (maxSUV ≥ 5.1) showed the better radiologic response than the low SUV group (maxSUV < 5.1). The median OS were 996.0 days in definitive group and 144.0 days in palliative group. Factors affecting OS were the %reduction of alpha-fetoprotein (AFP) level in the definitive group and Child-Pugh class in the palliative group. To predict the POF, maxSUV based on the cutoff value of 5.1 was the only significant factor in distant metastasis group. CONCLUSION: The results of this study suggest that the maxSUV of (18)F-FDG PET-CT may be a prognostic factor for treatment outcome and the POF after RT. A %reduction of AFP level and Child-Pugh class could be used to predict OS in HCC.